Gaining Insights into Inherited Bleeding Disorders of Complex Etiology in Pediatric Patients: Whole-Exome Sequencing as First-Line Investigation Tool - Bandini, Perla; Borràs, Nina; Berrueco, Ruben; Gassiot, Susanna; Martin-Fernandez, Laura; Sarrate, Edurne; Comes, Natàlia; Ramírez, Lorena; Hobeich, Carlos; Vidal, Francisco; Corrales, Irene (Thrombosis and Haemostasis, 2023)
Introduction Investigation of the molecular basis of inherited bleeding disorders (IBD) is mostly performed with gene panel sequencing. However, the continuous discovery of new related genes underlies the limitation of this approach. This study aimed to identify genetic variants responsible for IBD in pediatric patients using whole-exome sequencing (WES), and to provide a detailed description and reclassification of candidate variants.Material and Methods WES was performed for 18 pediatric patients, and variants were filtered using a first-line list of 290 genes. Variant prioritization was discussed in a multidisciplinary team based on genotype-phenotype correlation, and segregation studies were performed with available family members.Results The study identified 22 candidate variants in 17 out of 18 patients (94%). Eleven patients had complete genotype-phenotype correlation, resulting in a diagnostic yield of 61%, 5 (28%) were classified as partially solved, and 2 (11%) remained unsolved. Variants were identified in platelet (ACTN1, ANKRD26, CYCS, GATA1, GFI1B, ITGA2, NBEAL2, RUNX1, SRC, TUBB1), bleeding (APOLD1), and coagulation (F7, F8, F11, VWF) genes. Notably, 9 out of 22 (41%) variants were previously unreported. Variant pathogenicity was assessed according to the American College of Medical Genetics and Genomics guidelines and reclassification of three variants based on family segregation evidence, resulting in the identification of 10 pathogenic or likely pathogenic variants, 6 variants of uncertain significance, and 6 benign or likely benign variants.Conclusion This study demonstrated the high potential of WES in identifying rare molecular defects causing IBD in pediatric patients, improving their management, prognosis, and treatment, particularly for patients at risk of malignancy and/or bleeding due to invasive procedures.
Keywords: whole-exome sequencing; next-generation sequencing; inherited bleeding disorders; genotype-phenotype correlation; thrombocytopenia; children cohort